Filling gaps on the distribution of Rhinoclemmys punctularia (Daudin, 1801) (Testudines: Geoemydidae) in the state of Maranhão, Brazil - Pereira, Luana N.; Santos, Danusy L.; Vasconcelos, Tiago S. [UNESP]; Oda, Fabrício H. (Pensoft Publishers, 2013)
We present a new record of the spot-legged turtle (Rhinoclemmys punctularia) for the state of Maranhão, Brazil. This record fills a gap of 600 km between the easternmost record of the species (municipality of Timon, state of Maranhão) and Ananás (state of Tocantins). In addition, the present study reports the occurrence of R. punctularia in a physiognomy of Cerrado. © 2013 Check List and Authors.